(untitled) (Global Journal of Medical Research, 2023)
Obstructive sleep apnea and its associated risk factors can now be more easily identified by specialists in the oro-facial zone not only through clinical diagnosis but also with the help of new imaging tools such as CBCT or scanners Orthodontists who intervene at the intersection of the aero-digestive spheres have long had an excellent diagnostic tool called Cephalometrics which they systematically use on a daily basis For this reason they are best equipped to detect early morphological signs of possible apneas or indications that an individual may be prone to obstructive sleep apnea and or hypopnea and to recommend more specific examinations and consultations including a Polysomnography